Changes over time in teachers' interpersonal role identity. Issue 3 (27th May 2018) - van der Want, Anna C.; den Brok, Perry; Beijaard, Douwe; Brekelmans, Mieke; Claessens, Luce C. A.; Pennings, Helena J. M.
Abstract: Interpersonal relationships between teachers and students play a crucial role in teachers' professional identity, yet have hardly been focused on in research. This study aimed to explore teachers' interpersonal role identity over time by focusing on teachers' appraisals of classroom situations and the relation with their interpersonal identity standards. Semi-structured and video-stimulated interviews were conducted with 24 teachers in 2011 and 2013. Between 2011 and 2013, 18 teachers changed their appraisal and/or their identity standard. The appraisals of specific situations became less stressful, interpersonal identity standards showed more control and more affiliation and the match between the appraisals of specific situations and the interpersonal identity standards increased. The concept of role identities offered a promising theoretical framework for research on teacher identity and teacher–student relationships and at the same time can be a practical tool for supporting teachers' identity development.